TI_GERICHTE 90.2009.78 vom 26. April 2011 , Lesione del diritto di essere sentito - sopralluogo in contraddittorio - TI Tribunale d'appello (2011)
Lesione del diritto di essere sentito - sopralluogo in contraddittorio